The stability augmentation system for a helicopter landing on a vessel deck - Zugaj, M.; Topczewski, S.; Bibik, P.; Roslowicz, A.; Malecki, J. (My University, 2021)
The paper presents part of the results obtained in the HELIMARIS project (”Modification of an optionally piloted helicopter for maritime mission performance”) led by PZL Swidnik in cooperation with Warsaw University of Technology and CTO. In the paper, the automatic stability and augmentation system for helicopter landing on the moving vessel is presented. The model of the helicopter developed and evaluated in FLIGHTLAB software is using for analysis and synthesis of the control system algorithm. The simulation test on the system performances and robustness on the helicopter weight configuration as well as flight, environment and technical conditions are presented and discussed.